-9x-110=4x+72

Simple and best practice solution for -9x-110=4x+72 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9x-110=4x+72 equation:


Simplifying
-9x + -110 = 4x + 72

Reorder the terms:
-110 + -9x = 4x + 72

Reorder the terms:
-110 + -9x = 72 + 4x

Solving
-110 + -9x = 72 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-110 + -9x + -4x = 72 + 4x + -4x

Combine like terms: -9x + -4x = -13x
-110 + -13x = 72 + 4x + -4x

Combine like terms: 4x + -4x = 0
-110 + -13x = 72 + 0
-110 + -13x = 72

Add '110' to each side of the equation.
-110 + 110 + -13x = 72 + 110

Combine like terms: -110 + 110 = 0
0 + -13x = 72 + 110
-13x = 72 + 110

Combine like terms: 72 + 110 = 182
-13x = 182

Divide each side by '-13'.
x = -14

Simplifying
x = -14

See similar equations:

| 9(x+4)=3(x+24) | | .5c=2.25 | | 7n-1=5n+n | | 17.50=5.8x+3 | | X^2-X=21 | | 5(x-4)=25-4x | | 15=-3(-1+-4) | | -8y=120 | | -3x-5(2x-5)=6(3x-10) | | 3x+2x=5x^2 | | 2x-4=80x-10 | | (1.06)x=2000 | | 81=(t-(-4))+11 | | 3y-2y=1-2x | | b-2+8b=26 | | 113+3x+46+90=720 | | 2x-8=8-2x | | 4=5(54) | | 4(-2x)+6=14 | | 1-8=-9z | | (x+36)+2x+(x+36)+180=540 | | 5533+522522= | | 7n+30=2n-25 | | 15(1t+6m)+9t=6 | | 7x-24+5x+18=180 | | x^2-3x=29 | | (3f)+2=11 | | -8st+5t+2u-1=8t+9u-9 | | 170=45t | | 10b-9-3b=2 | | 170-t=45 | | 45=170t |

Equations solver categories